2022
DOI: 10.1097/mao.0000000000003777
|View full text |Cite
|
Sign up to set email alerts
|

Audiometry-Confirmed Sudden Sensorineural Hearing Loss Incidence among COVID-19 Patients and BNT162b2 Vaccine Recipients

Abstract: ObjectiveTo compare sudden sensorineural hearing loss (SSNHL) incidence rates over the coronavirus disease 2019 (COVID-19) outbreak and the COVID-19 vaccination campaign periods to pre-COVID-19 periods.Study DesignRetrospective cohort.SettingSecondary hospital.PatientsPatients >12 years with auditory-confirmed SSNHL were enrolled. COVID-19 status and BNT162 inoculation records ≤28 days before SSNHL diagnosis were retrieved. Patients were categorized according to their date of presentation over four equal perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In our report, we have shown that there was no clear association between COVID-19 patients and the BNT162b2 vaccination with an increased incidence of SSNHL (4). This leaves the reader the possibility to adhere to the notions that both endogenic and exogenic influences exist in the pathophysiology of this disease, but most likely, the BNT162b2 vaccination is not included among these, as is COVID-19.…”
mentioning
confidence: 51%
“…In our report, we have shown that there was no clear association between COVID-19 patients and the BNT162b2 vaccination with an increased incidence of SSNHL (4). This leaves the reader the possibility to adhere to the notions that both endogenic and exogenic influences exist in the pathophysiology of this disease, but most likely, the BNT162b2 vaccination is not included among these, as is COVID-19.…”
mentioning
confidence: 51%
“…There were fewer SSNHL instances during the first COVID-19 months, according to Cohen Michael et al (1). Although the SSNHL rate increased during the COVID-19 vaccination campaign, Cohen Michael et al (1) noted that it was not greater for individuals who got the BNT162b2 vaccine.…”
mentioning
confidence: 93%
“…Althoughthe SSNHL rate increased during the COVID-19 vaccination campaign, Cohen Michael et al(1) noted that it was not greater for individuals who got the BNT162b2 vaccine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a recent retrospective cohort study using electronic patient records at a secondary hospital in the Israeli city of Ashdod, it was shown that the incidence of audiometry-confirmed SSNHL was lower in vaccine recipients than in pre-pandemic unvaccinated patients. 6 …”
mentioning
confidence: 99%